Meningkatkan Kreativitas Belajar pada Pembelajaran PAKBP dengan Model PBL Fase C Kelas V Sekolah Dasar Negeri 11 Paat Kecamatan Embaloh Hulu - Petronila Merlin (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to increase the learning creativity of class V students in the subject of Catholic Religious Education and Character (PAKBP) through the application of the Phase C Problem Based Learning (PBL) model. PBL was chosen because it encourages students to be more active in solving real problems, thinking critically, and develop creativity. This classroom action research was carried out at the Paat 11 State Elementary School, Embaloh Hulu District, with a focus on the material